PENGELOLAAN PAJAK HOTEL DAN PAJAK RESTORAN DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) - Saputra, Fahri; Heriyanto, Meyzi; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2019)
Management of Hotel Taxes and Restaurant Taxes in the Context of Increasing Regional Original Income. This study aims to determine and analyze the management of hotel taxes and restaurant taxes by the Regional Office of Financial and Asset Management Revenue in Siak Regency in order to increase Regional Original Revenue. This study uses a qualitative descriptive method approach. Primary data was obtained directly through interviews from key informants, namely the Head of DPPKAD, Secretary of DPPKAD, Head of PAD and Balancing Funds, Section Head of Data Collection and Determination, Head of Billing and Receipt of Receipts, and Head of Objection Examination Section and Legislation. Secondary data is obtained from research documents. The results showed that the Siak Regency Government had made efforts to improve hotel tax management and restaurant taxes through intensification of hotel tax sources and restaurant taxes as well as extensification of hotel tax sources and restaurant taxes, but not yet optimal as cash inflows area.